2013
DOI: 10.1007/s12032-013-0663-z
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal carcinoma-derived fibroblasts modulate natural killer cell phenotype and antitumor cytotoxicity

Abstract: Substantial evidence indicates that cancer-associated fibroblasts (CAFs) are critical components in the process of cancer progression. However, the role of CAFs in the immunopathogenesis of human cancer remains elusive. In this study, we demonstrate that purified colorectal carcinoma-derived fibroblasts exhibit activated phenotypes characterized by substantial α-smooth muscle actin expression. These CAFs sharply suppress natural killer (NK) cell functions in co-culture experiments. In contrast, normal skin fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 31 publications
2
65
0
1
Order By: Relevance
“…This effect was dependent on both cell‐to‐cell contact and prostaglandin E2 (PGE2) released by TAFs. Another group confirmed our results by analyzing TAFs from HCC and colorectal carcinomas . Our study also suggested that NK cells present in melanoma lesions may reside in proximity to fibroblasts surrounding tumor nests, further suggesting a role for TAF in the inhibition of NK‐cell function in vivo .…”
Section: Tumor Microenvironment and The Evasion From Nk‐cell Attacksupporting
confidence: 86%
“…This effect was dependent on both cell‐to‐cell contact and prostaglandin E2 (PGE2) released by TAFs. Another group confirmed our results by analyzing TAFs from HCC and colorectal carcinomas . Our study also suggested that NK cells present in melanoma lesions may reside in proximity to fibroblasts surrounding tumor nests, further suggesting a role for TAF in the inhibition of NK‐cell function in vivo .…”
Section: Tumor Microenvironment and The Evasion From Nk‐cell Attacksupporting
confidence: 86%
“…Finally, it is important to point out that a pioneer study involving CAFs isolated from melanoma, but also other studies involving hepatocellular and colorectal carcinoma-derived fibroblasts, have shown that these cells can decrease NKp30, NKp44, DNAM-1 and/or NKG2D expression at the surface of NK cells, as well as PFN or GzmB expression [3436]. These effects seem to be dependent, at least partially, on the secretion of PGE2 and IDO by CAFs and lead to an attenuate cytotoxic activity of NK cells against their tumor target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the secretion of several chemokines by CAFs (including CXCL12/SDF1 and CCL2/MCP-1) can potentially attract macrophages in the tumor microenvironment and induce their differentiation into an M2 immunosuppressive phenotype [30, 31], and also allow the recruitment of immunosuppressive MDSC populations in the stroma [32, 33]. Finally, studies involving melanoma, hepatocellular and colorectal carcinoma-derived fibroblasts have shown that CAFs can decrease the expression of several NK activating receptors (including NKp30, NKp44 and NKG2D) on the NK cell surface through the secretion of prostaglandin E2 (PGE2) and/or indoleamine-2,3-dioxygenase (IDO) [3436] leading to an attenuate cytotoxic activity of NK cells against their tumor target cells.…”
Section: Introductionmentioning
confidence: 99%
“…67 In addition, CAFs significantly suppressed the cytotoxicity function of NK cells via releasing PGE2 in melanoma. 68 In the presence of NK cells, the CAF-induced expression of PGE2 was higher than fibroblasts, 64 suggesting that NK cells can also influence the cytokine expression of CAFs. However, studies of the influence of NK cells on CAFs are limited, and further studies are needed.…”
Section: Interaction Between Cancer-associated Fibroblasts and Mastmentioning
confidence: 99%